The Impact of Physical Activity and Healthy Lifestyle Patterns on Athletes' Mental Health - I Putu Agus Dharma Hita (Yayasan Adra Karima Hubbi, 2024)
This study aims to explore the impact of physical activity and healthy lifestyle on athletes' mental health. The literature review method was employed to collect, analyze, and synthesize related research findings. The results indicate that regular physical activity and a healthy lifestyle have significant positive effects on athletes' mental health. Physical activity helps reduce symptoms of depression and anxiety, improves mood, and enhances sleep quality. Healthy lifestyle practices, including good nutrition and stress management, also contribute to athletes' mental well-being. Psychosocial factors such as social support and positive training environments also play a crucial role in maintaining athletes' mental health. Based on these findings, it is recommended that the development of training programs and interventions in sports pay more attention to athletes' mental health aspects. These programs should be tailored to individual needs and encompass aspects of physical activity, healthy lifestyle, and adequate psychosocial support.